PENGARUH PAD, DAU, DAK, DAN DBH TERHADAP BELANJA DAERAH (Studi pada Pemerintah Daerah Kabupaten/Kota di Provinsi Jawa Timur) - Sari, Erlina Tiara Intan; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to test the influence of local revenue which consists of local own source revenue, generalallocation fund, special allocation fund, and profit sharing fund give influence to the local expenditure ofdistricts / cities in East java province in 2013-2015 periods. Quantitative method is used in this research as theresearch method. The samples are 35 districts / cities in East Java Province. The data is the secondary data whichhas been obtained from budget realization statement of districts / cities in East Java province in 2013-2015periods which has been obtained from The Audit Board of the Republic of Indonesia (BPK-RI) East javaprovince. Based on the test result, it has been found that: 1) local own source revenue give significant andpositive influence to the local expenditure. 2) General allocation fund give significant and positive influence tothe local expenditure. 3) special allocation fund give significant and negative influence to the local expenditure.4) Profit sharing fund give significant and negative influence to the local expenditure.Keywords: local own source revenue, general allocation fund, special allocation fund, profit sharing fund, localexpenditure.